Behavior of the inorganic chemistry of bituminous coals in the Checua - Lenguazaque syncline - Herrera Carvajal, David Alejandro; Rincón Bayona, John Elkin; Sánchez, Sandra Manosalva (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2021)
X - Ray Fluorescence Spectrometry is a technique that allows to obtain the percentages of the inorganic chemistry present in the coals of the western flank of the Checua - Lenguazaque syncline. Based on the results obtained, it is possible to determine the behavior of the inorganic chemistry of these coals, both in depth and in their extension, allowing a better understanding of the chemical variations and jointly determine the coals with better coking characteristics based on Fouling and Slagging factors.